Trend in Ammonia Excretion during Acclimatization of Adult Freshwater Red Hybrid Tilapia Oreochromis mossambicus (Peters, 1852) X Oreochromis niloticus (Linnaeus, 1758) in Different Salinities - Pradeep, P.J.; Srijaya, T.C.; Hussain, A.; Mithun, S.; Shaharom, F.; Chatterji, A. (Our Nature, 2012)
An attempt was made to study the trend in ammonia excretion by red hybrid tilapia during their acclimatization in seawater under slow and sudden conditions. Acclimatization of salinity 5 ppt showed an increase of ammonia level in water by 83.35% (7.69 mg/kg/l/day) as compared to the control group (P<0.05) whereas the value was 24.97% (10.25 mg/kg/l/day) at 10 ppt. The level of ammonia was dropped at salinity 15 ppt (5.12 mg/kg/l/day) by 50% and 25% at 20 ppt (3.84 mg/kg/l/day). The ammonia level with sudden transfer to different salinities were; 1.94, 1.38 and 2.77 mg/kg/l at 10, 20 and 30 ppt respectively, after 2 hrs of acclimatization whereas it reached to 11.11 mg/kg/l at 10 and 20 ppt within 24 hrs. All fishes were found dead within 3 hours of their sudden transfer to 30 ppt. The Results suggest that a gradual salinity increase is beneficial for acclimatizing marine tilapia. DOI: http://dx.doi.org/10.3126/on.v9i1.5730